Research of Light Use Efficiency for Paddy Rice Using Multi-Angle Hyperspectral Observations - Guo, Jianmao; Zhang, Zhanhao; Guo, Caiyun; Jin, Shuyuan (Frontiers in Earth Science, 2022)
Light use efficiency (LUE) is a critical variable for modeling gross primary production (GPP) of vegetation. The photochemical reflectance index (PRI) is based on reflectance at 531 and 570 nm, which has great potential in predicting the light use efficiency (LUE) and makes LUE related to plant optical characteristics. Despite the great achievement in understanding the correlation of PRI and LUE on forests, the application of PRI in estimating LUE on crops has almost been ignored. The present study reported the ability of multi-angle PRI to track eddy covariance (EC)-based LUE in a rice field in East China. We found that PRI can estimate LUE in sunny days (R2 = 0.4; p < 0.05). The correlation of PRI and LUE was greater than that at OZA of 0° (R2 = 0.4; p < 0.05) after distinguishing different OZAs and scatter directions and was the greatest in the backscatter direction with an OZA of 60° (R2 = 0.7; p < 0.01). This correlation was also corrected by the bidirectional reflectance distribution function (BRDF), where R2 = 0.72 after correction. We noted that the relationship between PRI and LUE on cloudy days was poor, where R2 = 0.26. Photosynthetically active radiation (PAR) had an influence on the LUE and PRI, while vapor pressure deficit (VPD) and air temperature (Ta) had negative influences on the correlation of PRI and LUE. Our research suggests that PRI can efficiently track the LUE of the rice growth period when considering environmental factors and rice canopy structures.